THE INFLUENCE OF SYSTEM QUALITY, INFORMATION QUALITY, AND SERVICE QUALITY ON USER SATISFACTION OF THE RUANGGURU APPLICATION IN WEST JAKARTA - Wijaya, Andi; Turangan, Joyce A. (International Journal of Application on Economics and Business, 2025)
The development of technology in the field of the internet has had an impact on innovation in education. The technological changes are increasingly favored because they are perceived as easier, time-saving, and can serve as an alternative to improving the quality of learning, knowledge, and academic achievement. The growing digitalization and widespread use of technology and the internet among the public have encouraged many people to use e-learning. Therefore, tutoring services have adapted to these changes, transitioning from traditional face-to-face sessions to online tutoring. However, despite the growing interest in online tutoring, it does not guarantee success for users compared to similar competitors. This study analyzes the factors influencing user satisfaction with tutoring services and their implications for net profit. The research tests three hypotheses using the structural equation model with a total of 150 respondents.